Modeling a mobile gamification model to increase student engagement: an analysis using analytic hierarchy process - Daud, Rafizah; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Mohd Yusoff, Azizul (American Scientific Publishers, 2017)
Points, Badges and Leader board most of the favourite gamification mechanics has been chosen by many researchers. The purpose of leader board is to view the top scores of players and it can be viewable by all the players. The bottom place in the scoreboard affected motivation in negative way. Some of researchers concluded that some of the students enjoyed the competition and some of them did not. Categorizing appropriate gaming elements for specific audience is difficult. To retain the player’s engagement, the design of the game mechanics must carefully balance so that learners can compete in each other and everyone has the chance to win. We present this study to determine the best gamification mechanics that will use in the mobile learning environment. Analysis Hierarchy Process (AHP) is used to determine top six gamification elements for three types of gamification instruction interaction dimension. This method breaks the decision making problem into a hierarchy. Then, a pair wise comparisons matrix will develop to establish the priorities among the elements in the hierarchy. This study involved 84 students from Community Colleague as a sample. The result shows that there are 6 gamification elements have been selected regarding the Global Priorities Distribution for criteria for each alternative which is Check points (0.2924) and Memory Game (0.2698) for Learner-Content Interaction. For learner-instructor interaction, the highest vote is Rewards (0.5712) and Trophies-Badges (0.2788). Team Leader board (0.3042) and Redeemable Points (0.2424) are nominated for learner-learner interaction. The weights of the criteria (Gamification Instruction Interaction Dimension) revealed that The Learner-Learner interaction (0.4394) is the most important criteria. The Consistency Ratio of this study is 0.08 is acceptable. The proposed conceptual model will be implementing in mobile learning environment to investigate the learning engagement in cognitive and behaviour for higher education level, as well as the relations between the mechanics and their assumed player types.